2018
DOI: 10.1016/j.im.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of social media in enhancing guanxi and perceived effectiveness of E-commerce institutional mechanisms in online marketplace

Abstract: This study extends literature on e-commerce trust and re-purchase intentions by exploring the role of swift guanxi and perceived effectiveness of institutional mechanisms (PEEIM) in the context of a Chinese e-marketplace-Taobao. We explore how Taobao's social media technologies (online reviews and instant messenger) can improve swift guanxi and PEEIM by increasing online interactivity and presence. We find that buyers' PEEIM negatively moderates trust in online sellers and repurchase intentions. We show that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(120 citation statements)
references
References 87 publications
(175 reference statements)
7
98
0
2
Order By: Relevance
“…Therefore, merchant trust for the m-payment transaction will reduce when there is perceived opportunism. (Chong et al 2018;Xin et al 2013).…”
Section: Mobile Service Provider (Msp) Characteristicmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, merchant trust for the m-payment transaction will reduce when there is perceived opportunism. (Chong et al 2018;Xin et al 2013).…”
Section: Mobile Service Provider (Msp) Characteristicmentioning
confidence: 98%
“…The concept of the halo effect is based on the explanation that an individual's perception or views about a product or a person is based on previous experiences and the sort of interpretation which leads to cognitive bias. For instance, one can explain that Apple's other products are successful and people have confidence in it, due to the positive influence and how successful iPod was (Chong et al 2018;Wilcox 2008). Thus, merchant perceptions on MSP as fair and honest translates to beliefs and trust for the mobile payment system controlled by the MSP.…”
Section: Mobile Service Provider (Msp) Characteristicmentioning
confidence: 99%
See 1 more Smart Citation
“…The research results indicate that the interaction of social commerce is an important factor influencing the formation of strong connection. Chong et al (2018) found that perceiving the effectiveness of the e-commerce institutional mechanism would negatively regulate users' trust in online sellers and repurchase intentions.…”
Section: Factors Influencing User Purchase In Social Commercementioning
confidence: 99%
“…Social commerce, as the interaction of social media and e-commerce, has gained popularity over the last years. It does not only provide good resources for consumers to improve purchase decisions, but also offers an innovative and efficient approach for companies to gain business value [5,15,16]. There is a demand to extend this stream of research and provide further insights into the phenomenon and its implementations for business practices.…”
Section: Social Commercementioning
confidence: 99%